Mechanisms of pathogenicity and the quest for genetic modifiers of kidney disease in branchiootorenal syndrome - Sewerin, Sebastian; Aurnhammer, Charlotte; Skubic, Cene; Cokan, Kaja Blagotinšek; Jeruc, Jera; Rozman, Damjana; Pfister, Frederick; Dittrich, Katalin; Mayer, Brigitte; Schönauer, Ria; Petzold, Friederike; Halbritter, Jan (Clinical Kidney Journal, 2024)
Backgound. Branchiootorenal (BOR) syndrome is an autosomal dominant disorder caused by pathogenic EYA1 variants and clinically characterized by auricular malformations with hearing loss, branchial arch anomalies, and congenital anomalies of the kidney and urinary tract. BOR phenotypes are highly variable and heterogenous. While random monoallelic expression is assumed to explain this phenotypic heterogeneity, the potential role of modifier genes has not yet been explored. Methods. Through thorough phenotyping and exome sequencing, we studied one family with disease presentation in at least four generations in both clinical and genetic terms. Functional investigation of the single associated EYA1 variant c.1698+1G>A included splice site analysis and assessment of EYA1 distribution in patient-derived fibroblasts. The candidate modifier gene CYP51A1 was evaluated by histopathological analysis of murine Cyp51+/− and Cyp51−/− kidneys. As the gene encodes the enzyme lanosterol 14α-demethylase, we assessed sterol intermediates in patient blood samples as well. Results. The EYA1 variant c.1698+1G>A resulted in functional deletion of the EYA domain by exon skipping. The EYA domain mediates protein-protein interactions between EYA1 and co-regulators of transcription. EYA1 abundance was reduced in the nuclear compartment of patient-derived fibroblasts, suggesting impaired nuclear translocation of these protein complexes. Within the affected family, renal phenotypes spanned from normal kidney function in adulthood to chronic kidney failure in infancy. By analyzing exome sequencing data for variants that potentially play roles as genetic modifiers, we identified a canonical splice site alteration in CYP51A1 as the strongest candidate variant. Conclusion. In this study, we demonstrate pathogenicity of EYA1 c.1698+1G>A, propose a mechanism for dysfunction of mutant EYA1, and conjecture CYP51A1 as a potential genetic modifier of renal involvement in BOR syndrome.
CRIS-Team Scopus Importer:2024-01-26
Keywords: branchiootorenal syndrome; chronic kidney disease; modifier genes; patient-derived fibroblasts; phenotypic heterogeneity